Becoming the Baptized Body : Disability and the Practice of Christian Community - Barton, Sarah Jean, 1986- (Book collections on Project MUSE., 2022)
"Explores how baptismal theologies and practices shape Christian imagination, identity, and community, through privileging the perspectives and stories of Christians with intellectual disabilities"--